Confirmatory factor analysis of a rubric for assessing algorithmic thinking on undergraduate students - Eduardo Adam Navas-López (Universidad ORT Uruguay, 2024)
Algorithmic thinking is a key element for individuals to be aligned with the computer era. Its study is important not only in the context of computer science but also in mathematics education and all STEAM contexts. However, despite its importance, a lack of research treating it as an independent construct and validating its operational definitions or rubrics to assess its development in university students through confirmatory factor analysis has been discovered. The aim of this paper is to conduct a construct validation through confirmatory factor analysis of a rubric for the algorithmic thinking construct, specifically to measure its level of development in university students. Confirmatory factor analysis is performed on a series of models based on an operational definition and a rubric previously presented in the literature. The psychometric properties of these models are evaluated, with most of them being discarded. Further research is still needed to expand and consolidate a useful operational definition and the corresponding rubric to assess algorithmic thinking in university students. However, the confirmatory factor analysis confirms the construct validity of the rubric, as it exhibits very good psychometric properties and leads to an operational definition of algorithmic thinking composed of four components: Problem analysis, algorithm construction, input case identification, and algorithm representation.